Comparing the Efficacy of Weekly Azathioprine Pulse versus Betamethasone Oral Mini-Pulse in the Treatment of Moderate to Severe Alopecia Areata: Azathioprine versus Betamethasone in Alopecia - Usman, Kainat; Shahzad, Muhammad Khurram; Hassan, Tahir; Jamil, Muhammad Irfan; Nadeem, Muhammad (Pakistan Journal of Health Sciences, 2025)
Alopecia Areata (AA) is a disease that leads to unpredictable hair loss. Objective: To assess and compare the efficacy of Weekly Azathioprine Pulse (WAP) versus Betamethasone Oral Mini-Pulse (BOMP) therapy in Alopecia areata. Methods: Sixty patients with ≥15% scalp involvement were divided into two groups. The WAP group given azathioprine (300 mg) once weekly; the BOMP group received betamethasone (5 mg) on two consecutive days weekly. A randomized controlled trial was performed at the Dermatology Department of Sheikh Zayed Hospital, Rahim Yar Khan, over a 6-month (March–September 2023). Both treatments continued for 12 weeks. At baseline, 12 weeks, and 12 weeks post-treatment SALT scores were recorded. Efficacy was defined as ≥75% hair regrowth. Results: The male-to-female ratio was 1.9:1 with 39 (65%) males and 21 (35%) females. WAP group baseline SALT score of 42.60 ± 13.75 decreased to 13.97 ± 11.79 after a follow-up period of 12 weeks post-treatment, compared to BOMP group reduction from 38.67 ± 10.76 to 21.63 ± 10.96; regrowth percentage was higher in WAP (68.62%) vs. BOMP (44.28%), p=0.001. In the WAP group, 13 (43.3%) of patients achieved efficacy with ≥76% hair regrowth, compared to 3 (10%) in the BOMP group, showcasing a significant disparity (p-value=0.009). Relapse at three months occurred in 1 (3.3%) participant in the WAP group and 2 (6.7%) participants in the BOMP group (p-value of 0.500). Conclusion: This study demonstrated that WAP therapy was superior to BOMP in moderate to severe AA with notable hair regrowth.